INFLUENCE OF IONIC PROCESSING ON CHANGES IN INITIAL SURFACE ROUGHNESS OF SAMPLES MADE OF D16T ALLOY - S. A. Ivaschenko; S. G. Koida (Наука и техника)
Results of the investigations pertaining to study of influence of technological ionic processing process parameters on changes in an initial roughness of samples made of D16Т alloy are provided in the paper.The paper shows that bombardment by high-energy Ti+-ions is effective at processing a surface with a high initial roughness and is not suitable for processing surfaces after grinding and polishing. It is necessary to use low-energy ions of inert gases for processing a surface with a low initial roughness